2008
DOI: 10.3200/jach.57.2.173-182
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Among College Students: Do Those Who Need Services Know About and Use Them?

Abstract: With the high prevalence rates and severity of mental health problems, university mental health providers must continue to make strategic efforts to disseminate knowledge about mental health services to all students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
80
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 47 publications
7
80
1
3
Order By: Relevance
“…7,8,15 All students, regardless of year group, experienced varying degrees of stress while studying and this accords with the findings of Chew-Graham. 16 The majority of students whose mental wellbeing was affected negatively while undertaking the course did not seek help, which supports the view of Yorgason et al 17 They confirm that, although student populations experience various forms of stress, only a small number actively seek any professional help.…”
Section: Discussionsupporting
confidence: 73%
“…7,8,15 All students, regardless of year group, experienced varying degrees of stress while studying and this accords with the findings of Chew-Graham. 16 The majority of students whose mental wellbeing was affected negatively while undertaking the course did not seek help, which supports the view of Yorgason et al 17 They confirm that, although student populations experience various forms of stress, only a small number actively seek any professional help.…”
Section: Discussionsupporting
confidence: 73%
“…Secondly, it targets to identify the correlation and differences of past experiences, consciousness, attitude and perceived barriers to accessing counselling services with the aim to use counselling services among students between local and international students. Yorgason, Linville, and Zitzman (2008) reported that between 30% and 60% of the American college students were actually unaware or unsure regarding the availability of campus mental health services. Further, there are only 14% of the respondents know exactly where their university's counselling centre is.…”
Section: Introductionmentioning
confidence: 99%
“…Відповідно до міри вираженості симптому кожному пункту присвоєні значен-ня від 0 (симптом відсутній, або виражений мінімально) до 3 (максимальна вира-женість симптому). Деякі категорії уміщують альтернативні твердження, що ма-ють еквівалентну питому вагу (ACHA-NCHA-II, 2016;Christensson et al, 2011;Shih & Eberhart, 2008;Waghachavare et al, 2010;Yorgason et al, 2008); 3) методика дослідження самооцінки Дембо-Рубінштейн заснована на без-посередньому оцінюванні обстежуваними низки особистих якостей, таких як здоров'я, здібності, характер тощо. Обстежуваним пропонується на вертикальних лініях відзначити певними знаками рівень розвитку у них цих якостей (показник самооцінки) і рівень домагань, тобто рівень розвитку цих же якостей, який би за-довольняв їх.…”
unclassified